Mixed neuroendocrine-non-neuroendocrine tumour of pancreas mimicking groove pancreatitis: Case report. (November 2021) - Dhali, Arkadeep; Ray, Sukanta; Ghosh, Ranajoy; Sinha, Mamata Guha Mallick; Khamrui, Sujan; Dhali, Gopal Krishna
Abstract: Introduction: Mixed neuroendocrine-non-neuroendocrine neoplasm (MiNEN) is a rare tumour of the pancreas which can mimic groove pancreatitis. Case report: We present a 49-year-old Indian male presented with constant, dull-aching epigastric pain for last 6 months radiating to back, not associated with jaundice, gastrointestinal bleed, fever or weight loss. He also had history of alcohol abuse for last 15 years. Physical examination was unremarkable. Laboratory investigations were within normal limits. Contrast enhanced computed tomography (CT) of the abdomen was suggestive of groove pancreatitis. CA 19.9, CEA and IgG4 levels were normal. Upper gastrointestinal endoscopy revealed an oedematous mucosa with narrowing of second part of duodenum. Endoscopic ultrasound (EUS) showed bulky pancreas with ill-defined heteroechoic head with periduodenal soft tissue thickening. EUS guided fine needle aspiration revealed chronic inflammatory cells. Based on the endoscopic findings and imaging, we suspected the diagnosis to be groove pancreatitis. He underwent open Whipple's pancreaticoduodenectomy. Histopathological evaluation revealed well differentiated neuroendocrine tumour and immunohistochemistry revealed features which was consistent with mixed neuroendocrine-non-neuroendocrine tumour (MiNEN). Post-operative period was uneventful and he was discharged on post-op day 7. A PET-CT scan was done to look for any silent metastasis and it was negative. He recieved 4 cycles of cisplatin-based chemotherapy. He was symptom free and doing well on 12 months follow up with no evidence of recurrence in surveillance CT imaging. Discussion: Pancreatic MiNEN is characterised by presence of two malignant tissues, adenocarcinoma and NET, with one constituent involving at least 30% of the tumour. We report the pitfalls in diagnostic work-up which can lead to misdiagnosis of this rare entity. Specially due to admixture of different kinds of tissue, radiological investigations can be misleading. Conclusion: Our case highlights the fact that MiNEN of pancreas can mimic a benign condition like groove pancreatitis. If routine histopathological and immunohistochemical evaluation is not done on the resected samples, relying on radiological and fine-needle aspiration cytology evidences, the actual diagnosis could be missed. Highlights: MiNEN of pancreas is a rare pathology and difficult to diagnose preoperatively. MiNENs should be considered as a differential for groove pancreatitis. Histopathology with immunohistochemistry should be done for all pancreatoduodenectomy specimen to diagnose such rare tumors.